THE PHILOSOPHICAL AND LEGAL FOUNDATIONS OF HALAL PRODUCT LEGISLATION IN INDONESIA: A SYARI‘AH AND POSITIVE LAW PERSPECTIVE - Abd. Hafid; Siradjuddin; Rika Dwi Ayu Permitasari; Asni Zubair; Firdaus Firdaus; Asdiansyah (Jurnal Al-Kharaj: Studi Ekonomi Syariah, Muamalah, dan Hukum Ekonomi, 2025)
Indonesia, as the world's largest Muslim-majority nation, represents a unique case in integrating Sharī‘ah principles into national legal frameworks, particularly in the regulation of halal products. With more than 86 percent of its population adhering to Islam, the demand for halal assurance is not merely a matter of religious observance but a fundamental consumer right embedded within both moral philosophy and constitutional Law. This article explores the philosophical and legal foundations of halal product legislation in Indonesia through a dual perspective—Sharī‘ah and positive Law. The study employs a normative-empirical approach grounded in maqāṣid al-sharī‘ah analysis and legal positivism, examining how these epistemic frameworks converge in Law No. 33 of 2014 concerning Halal Product Assurance (Undang-Undang Jaminan Produk Halal, UU JPH). It further analyzes the institutional synergy between the Ministry of Religious Affairs, the Halal Product Assurance Organizing Agency (Badan Penyelenggara Jaminan Produk Halal, BPJPH), and the Indonesian Ulema Council (MUI), assessing their shared role in enforcing ethical-economic equilibrium. Empirical data from 2019 to 2025 reveal that Indonesia's halal-certified products and exports have increased significantly, reflecting the effectiveness of the hybrid regulatory model. The findings highlight that the Indonesian halal system, while rooted in Islamic jurisprudence, also embodies constitutional rationality, where the State plays an active role in safeguarding the moral economy through Law. Ultimately, this research concludes that Indonesia's halal legislation manifests the synthesis of divine command ethics and public policy rationalism, symbolizing the philosophical unity between religion and State in protecting human dignity and consumer welfare.